A Roadmap for Climate Action in Latin America and the Caribbean, 2021-2025 - World Bank Group (Washington, DC: World Bank, 2022)
In Latin America and the Caribbean (LAC) the rapidly changing climate is increasing the frequency and intensity of extreme weather‑related events. The year 2020 saw the most catastrophic fire season over the Pantanal region and a record number of storms during the Atlantic cyclone season. Eta and Iota, two category 4 hurricanes, affected more than 8 million people in Central America, causing tens of billions of dollars in damage. In Honduras, annual average losses due to climate‑related shocks are estimated at 2.3 percent of gross domestic product (GDP). In rankings of the impacts of extreme weather events from 2000 to 2019, five Caribbean nations figure among the top 20 globally in terms of fatalities per capita, while in terms of economic losses as a share of GDP eight of the top 20 countries are in the Caribbean. Extreme precipitation events, which result in floods and landslides, are projected to intensify in magnitude and frequency due to climate change, with a 1.5°C increase in mean global temperature projected to result in an increase of up to 200 percent in the population affected by floods in Colombia, Brazil, and Argentina; 300 percent in Ecuador; and 400 percent in Peru. Climate shocks reduce the income of the poorest 40 percent by more than double the average of the LAC population and could push an estimated 2.4–5.8 million people in the region into extreme poverty by 2030.